Kualitas Pelayanan BPJS Kesehatan di Masa Pandemi Covid-19 - Muchti Yuda Pratama; Ida Yustina; Nurmaini Nurmaini; Zulkarnain Zulkarnain (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
This study aims to analyze the quality of BPJS Health services during the COVID-19 pandemic at the Mampang Health Center based on the dimensions of Tangible, Reliability, Responsiveness, Assurance and Empathy. This research design uses a quantitative approach with a descriptive type of research. The location of this research is the Mampang Public Health Center, Kotapinang District, South Labuhanbatu Regency. Based on the results of the research conducted by researchers on 150 respondents who were patients or participants who visited the Mampang Public Health Center, Kotapinang District using BPJS Health, the results were (88.6%) rated moderate on Tangible dimensions, (85.7%) assessed on the Reliability dimension, (94.3%) rated it moderate on the Responsiveness dimension, (82.9%) rated it moderate on the Assurance dimension, and (97.1%) rated yes it meets the Empathy dimension. None of the respondents' statements stated that the quality of service was poor even though they were BPJS users.